Strategi Guru Pendidikan Agama Islam dalam Membentuk Kepribadian Islami Peserta Didik di SMP Negeri 24 Padang - Retna Sari; Rengga Satria (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
This study aims to examine: 1) Strategies of Islamic Religious Education Subject Teachers in Shaping Islamic Personality towards Students at SMPN 24 Padang. 2) Students' evaluation of the strategy of Islamic Religious Education subject teachers in shaping students' Islamic personalities. 3) Inhibiting factors and supporting factors of Islamic Religious Education subject teachers in shaping students' Islamic personalities at SMPN 24 Padang. The method used in the research that has been carried out is a qualitative research group with a descriptive approach. This research was conducted at SMPN 24 Padang. Data was collected using techniques including observation, documentation, and interviews. Based on the results of the research that has been carried out, the following conclusions are obtained: 1) The strategy used by teachers of Islamic Religious Education subjects in shaping Islamic personality in terms of worship and morals is by using strategies through exemplary methods, habituation, and also advice. 2) Evaluation of students on the strategy of teachers of Islamic Religious Education subjects in shaping the Islamic personality of students at SMPN 24 Padang, namely by always controlling the behavior and worship of students. 3) Supporting factors in shaping the Islamic personality of students are the school, especially the principal, teachers, guardians of students, and also the surrounding community. 4) Then the inhibiting factors are the level of willingness of the students themselves, the use of gadgets, the environment of their friends, and also the family environment.